A Psycholinguistics Analysis: How do ESL Learners in Higher Education Write Paragraphs? - Faridatun Nida (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
Having the ability to write paragraphs is important, especially for students in higher education. Nevertheless, mastering the skill of writing is not easy, takes time, and sometimes is boring. Looking for the alternative leads the researcher to do research with the aim of finding the favorite topics of writing and understanding the difficulties in writing a paragraph using the psycholinguistics approach. Students are firstly given an explanation about the paragraph including the intrinsic and extrinsic elements of it. Then, they are instructed to write a paragraph in several steps but are free to choose their own topics. Their works then are analyzed in order to see the topic chosen by the students in writing paragraphs. Next, the analysis is focused on the structure and the ideas they deliver through the sentences. The results show that the topics chosen are about things related to their real life, like health, technology, food, sport, and natural disaster. Meanwhile, dealing with the structures and the ideas, the students’ works are divided into five categories. The two dominant categories are expected structure but unexpected content, and expected structure and expected content. Hence, the findings will be taken into the consideration for the lesson material. Besides, the student’s skill of writing and their problem in writing that is shown by the analysis of structure and content will be the focus of lesson discussion. Therefore, the students are expected to have fun learning in writing.